Modulation of the anti-tumor immune response by complement - Markiewski, Maciej M. (2008)
The involvement of complement activation products in promoting tumor growth has not yet been recognized. Here we show that generation of complement C5a in the tumor microenvironment enhanced tumor growth by suppressing the anti-tumor CD8(+) T cell-mediated response. This suppression was associated with the recruitment of myeloid-derived suppressor cells (MDSCs) into tumors and augmentation of their T cell-directed suppressive capabilities. Amplification of MDSC suppressive capacity by C5a occurred through regulation of the production of reactive oxygen and nitrogen species. Pharmacological blockade of C5a receptor significantly impaired tumor growth to a degree comparable to the effect produced by the anti-cancer drug Taxol. Thus, this study demonstrates a therapeutic role for complement inhibition in the treatment of cancer.